Rancang Bangun Robot Pengering Lantai Otomatis Menggunakan Metode Fuzzy - derisma, derisma (Jurnal Sistem Komputer, 2016)
The purpose of this research is to design and build a robot to dryer floor with automatic and moving regulary based on set of poin already control until can move like zig-zag. The robot is consist of mikrokontroler, motor shield as like driver motor, 2 sensor of ultrasonic, and motor of mop to dryer the floor. To control the movement use fuzzy logic with segeno method. Input from fuzzy logic and there are two kind of fuzzy logic, first is â€œerrorâ€ and the second is â€œ âˆ† errorâ€. Itâ€™s from sensor of ultrasonic, after procure of data so the mikrokontroler will process it, and then the output itâ€™s like value of PWM in order to moves and organize DC motor in order to be able to move straight, turn right, and turn left. After done testing and analysis, the level of success from motor of mop to moves with automatic as big as 80% because of effect the extent of the liquid found.